Oxygen assisted butanol conversion on bifunctional carbon nanotube catalysts: Activity of oxygen functionalities - Li, Fan; Yan, Pengqiang; Herold, Felix; Drochner, Alfons; Wang, Haihua; Cao, Tianlong; Liu, Weijie; Dai, Xueya; Zhang, Bingsen; Etzold, Bastian J.M.; Qi, Wei (Carbon, 2020)
Catalytic conversion of n-butanol to high-value-added product is considered as a highly important route towards biomass derived fine chemicals. The present work reports the applications of non-metallic multi-walled carbon nanotube (CNT) as bifunctional catalysts for oxygen assisted n-butanol conversion reactions. Oxidative dehydrogenation (ODH) and dehydration of n-butanol on CNT yielded aldehyde and alkene compounds via redox and acid catalytic routes, respectively. CNT exhibited high activity (over 50% n-butanol conversion) and stability (over 120 h) under gentle reaction conditions (<330 °C), which are competitive to conventional metal-based catalysts. Carboxylic acid groups were identified as catalytic active sites for dehydration reactions via linking the reactivity (kinetic parameters) with the surface composition and structural information of CNT catalysts. The redox activity could be related to ketonic carbonyl groups, and interestingly the intrinsic ODH catalytic activity is also influenced by degree of graphitization for CNT materials.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbon catalysis; n-Butanol conversion; Oxidative dehydrogenation; Oxygen functionalities; Reaction mechanism and kinetics